2022
DOI: 10.3390/nu14214473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Specific Collagen Peptide Food Supplement on Periodontal Inflammation in Aftercare Patients—A Randomised Controlled Trial

Abstract: This controlled clinical trial evaluated the impact of a specific collagen peptide food supplement on parameters of periodontal inflammation in aftercare patients. Methods: A total of 39 study patients were enrolled. At baseline, bleeding on probing (BoP; primary outcome), gingival index (GI), plaque control record (PCR), recession (REC) and probing pocket depth (PPD) for the calculation of the periodontal inflamed surface area (PISA) were documented. After subsequent professional mechanical plaque removal (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Periodontal recall patients with a history of treated periodontitis who received collagen peptides after professional mechanical debridement showed significantly lower gingival bleeding and periodontal inflamed surface area (PISA) compared to patients who received professional mechanical debridement and placebo, decreasing the risk of re-activation of periodontitis [40]. The adjunctive intake of a nutraceutical agent containing baicalin (Neuridase ® , Enfarma SRL, Misterbianco, Italy) with SRP in patients with moderate periodontitis significantly decreased PPD and BoP but also pain after SRP, compared to SRP and placebo [41]. More studies on nutraceutical agents and other micronutrient supplements are needed to better evaluate their adjunctive effect on periodontal therapy.…”
Section: Vitaminsmentioning
confidence: 99%
“…Periodontal recall patients with a history of treated periodontitis who received collagen peptides after professional mechanical debridement showed significantly lower gingival bleeding and periodontal inflamed surface area (PISA) compared to patients who received professional mechanical debridement and placebo, decreasing the risk of re-activation of periodontitis [40]. The adjunctive intake of a nutraceutical agent containing baicalin (Neuridase ® , Enfarma SRL, Misterbianco, Italy) with SRP in patients with moderate periodontitis significantly decreased PPD and BoP but also pain after SRP, compared to SRP and placebo [41]. More studies on nutraceutical agents and other micronutrient supplements are needed to better evaluate their adjunctive effect on periodontal therapy.…”
Section: Vitaminsmentioning
confidence: 99%
“…In periodontal recall patients, the additional consumption of targeted collagen peptides has the potential to further augment the anti-inflammatory impact of professional mechanical plaque removal [79]. A rat study suggested that the whey component of milk protein promoted bone collagen synthesis, improved bone strength, and prevented alveolar bone loss by elevating hydroxyproline levels, thereby enhancing bone integrity [80,81].…”
Section: Sarcopenia and Periodontitismentioning
confidence: 99%